Airway Y-stent Insertion in Tracheobronchomalacia: A New Experience - Kuan, Yeh Chunn; How, Soon Hin; Ng, Teck Han; Liam, C K; Ahmad, Mohd Ashri; Abdul Rani, Mohammed Fauzi (The Faculty of Medicine, International Islamic University Malaysia, 2012)
This case report describes a rigid bronchoscopy-assisted placement of a silicone airway Y-stent in a patient who developed tracheobronchomalacia following repeated dilatations for post-tuberculous airway stenosis. This is the first report of an airway Y-stent insertion in Malaysia.